The influence of work stress, work motivation, and time management on work life balance in students who study while working - Made Mulyadi; Ni Luh Ayu Puspayanti; Luh Gede Elvina Adi Saputri (Institute of Computer Science (IOCS), 2024)
Studying while working creates its own challenges for each individual, such as the process of studying and working which takes up time and energy. The aim of this research is to determine the influence of work stress, work motivation, and time management on work life balance. The data used is primary and secondary data which will be obtained from distributing questionnaires. The number of samples used in this research was 85 respondents. The data collection technique used was in the form of a questionnaire. The analysis technique uses multiple linear regression. The results of this research are that work stress, work motivation, and time management simultaneously have a significant effect on work life balance. Work stress partially has a negative and significant effect on work life balance. Work motivation partially has a positive and significant effect on work life balance. Time management partially has a positive and significant effect on work life balance